Adjustment and Academic Achievement of Senior Secondary School Students; A Corelational Study (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This study examines the relationship between adjustment and academic achievement among senior secondary students in Ghaziabad City, focusing on both male and female students. A sample of 200 students (100 rural and 100 urban) from government-aided schools affiliated with the Utter Pradesh Madhyamik Shiksha Parishad Prayagraj were selected through random sampling. The Adjustment Inventory by A.K.P. Sinha and R.P.Singh was used to assess emotional, social, and educational adjustment. The findings indicate a low but significant positive correlation between adjustment and academic achievement at the 0.01 level. However, locale specific analysis revealed significant correlation for students belongs to urban areas at the 0.01 level, while students belongs to rural areas showed a significant positive low correlation between adjustment and achievement. These results suggest that adjustment plays a crucial role in academic performance, particularly for those students who are belong to rural and urban areas. The study highlights the importance of fostering well-being and well adjustment.